2016
DOI: 10.1002/ejic.201600426
|View full text |Cite
|
Sign up to set email alerts
|

Silica Functionalized by Bifunctional Dendrimers: Hybrid Nanomaterials for Trapping CO2

Abstract: Three types of poly(phosphorhydrazone) dendrimeric structures bearing function(s) suitable for grafting to silica and trapping CO 2 have been grafted to different types of silica with various textural properties (e.g., different surface areas, porous or nonporous, pore sizes). These hybrid hard/soft [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The introduction of ethoxysil groups into the roots of the dendron enables sol-gel hydrolysis and polycondensation, creating thus a dendritic stationary phase bonded to the column walls, characterized by remarkable uniformity and a roughened, porous appearance ( Figure 7 ). Various types of bifunctional poly(phosphorhydrazone) dendrons and dendrimers were likewise modified by triethoxysilyl moieties for grafting to silica and by amines for trapping CO 2 [ 84 ].…”
Section: Methods Of Preparationmentioning
confidence: 99%
“…The introduction of ethoxysil groups into the roots of the dendron enables sol-gel hydrolysis and polycondensation, creating thus a dendritic stationary phase bonded to the column walls, characterized by remarkable uniformity and a roughened, porous appearance ( Figure 7 ). Various types of bifunctional poly(phosphorhydrazone) dendrons and dendrimers were likewise modified by triethoxysilyl moieties for grafting to silica and by amines for trapping CO 2 [ 84 ].…”
Section: Methods Of Preparationmentioning
confidence: 99%
“…Then the Boc-protected amines were deprotected with trifluoroacetic acid (10%) in dichloromethane, followed by several washings. Measurements of CO 2 trapping showed that this compound was active, but not the most active of the series, probably because it penetrated too far inside the pores of silica due to its small size [ 32 ].…”
Section: Dendrons Based Onab 5 Derivatives Of N 3 P 3 As Core and Their Use For mentioning
confidence: 99%
“…The introduction of ethoxysil groups into the roots of the dendron enables sol-gel hydrolysis and polycondensation, creating thus a dendritic stationary phase bonded to the column walls, characterized by remarkable uniformity and a roughened, porous appearance ( Figure 7). Various types of bifunctional poly(phosphorhydrazone) dendrons and dendrimers were likewise modified by triethoxysilyl moieties for grafting to silica and by amines for trapping CO2 [78]. Another variation that involves reaction with activated rough surfaces and subsequent sol-gel siloxane bond formation, exploits the selectivity potential of hyperbranched PEI by grafting onto the surface of a magnetic porous ceramic [79].…”
Section: Attachment Of Polymers With Covalent Bonds To the Surface Ofmentioning
confidence: 99%